Le père Fraisse (1912-2001) Les combats d'un jésuite foudroyé - Comte, Bernard (Chrétiens et Sociétés. Documents et Mémoires, 2020)
In 1957, Father Fraisse was a student chaplain in Lyon. An original personality, he had had an exceptional career as a Resistance fighter in 1940 and 1944-45. Without having been alerted beforehand, he was sanctioned by the Company's Visitor who accused him of not giving the students a sense of hierarchical authority. He was exiled to Nice and forbidden to work with students and to do any ministry in Lyon. At the end of 1960, his return to Lyon was only a half measure: he was never rehabilitated and several painful cases show that he remained suspect in the eyes of some of his colleagues. His case is a striking example of the impact on the Church in France of the Roman stiffening at the end of the pontificate of Pius XII. Indeed, a "totalitarian" practice of religious obedience often had heavy human consequences. This authority condemned, often on the basis of denunciations, without the possibility for the accused to know his (secret) file and thus to defend himself. Fr. Fraisse's painful experience highlights some of the ways in which a cold war Church could lead to serious abuses. His friend and defender, Fr Ganne, opposed the concept of an authority respectful of justice and the rights of conscience, a conscience dear to Newman, who was a major reference for Fr Fraisse. And he also preached a Church open to the world. Today clericalism is questioned: Fraisse's life seems to have escaped this. His behaviour, his theology, but also the importance of his friendships with lay people and their role in the development of his thought, anticipate the future. Witness the first two posthumous books of Fr Ganne that he published, not without difficulty: Qui dites-vous que je suis? Lessons on Christ and The Gift of the Spirit Lessons on the Holy Spirit.